PENGARUH BRAND IMAGE, KUALITAS PRODUK DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN PADA KEDAI MBA JUS DI KOTA PALOPO (Jurnal Riset Manajemen dan Akuntansi, 2023)
This research analyzes the influence of brand image, product quality and price on consumer purchasing decisions at the Mba Jus shop in Palopo City. The research method used is regression analysis using SPSS. The results of this research show that brand image has no influence and is not significant on purchasing decisions. This means that if the Brand Image decreases, it will reduce Purchasing Decisions but it is not significant. Product quality has no effect and is not significant on purchasing decisions. This means that if product quality decreases, it will reduce purchasing decisions but not significantly. Price has a significant effect on purchasing decisions. This means that the better the price, the purchase decision will increase significantly. Brand Image, Product Quality and Price simultaneously have a significant influence on Purchasing Decisions. This means that simultaneously the better the Brand Image, the better the Product Quality and the better the Price of a product, the greater the Purchase Decision.